2010
DOI: 10.1186/1471-2202-11-51
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of L-3-hydroxybutyryl-CoA dehydrogenase activity and circulating ketone body levels by pantethine. Relevance to dopaminergic injury

Abstract: BackgroundThe administration of the ketone bodies hydroxybutyrate and acetoacetate is known to exert a protective effect against metabolic disorders associated with cerebral pathologies. This suggests that the enhancement of their endogenous production might be a rational therapeutic approach. Ketone bodies are generated by fatty acid beta-oxidation, a process involving a mitochondrial oxido-reductase superfamily, with fatty acid-CoA thioesters as substrates. In this report, emphasis is on the penultimate step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…Therefore, in spite of its simple linear structure, this well‐tolerated low‐molecular‐weight compound displays a large array of mechanisms and functions that make it a very useful tool for cellular investigation and therapeutic intervention. Pantethine addresses essential cellular pathway, however, with few side effects since, as shown in the MPTP model of Parkinson's disease, it moderates pathological but not physiological processes (Cornille et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in spite of its simple linear structure, this well‐tolerated low‐molecular‐weight compound displays a large array of mechanisms and functions that make it a very useful tool for cellular investigation and therapeutic intervention. Pantethine addresses essential cellular pathway, however, with few side effects since, as shown in the MPTP model of Parkinson's disease, it moderates pathological but not physiological processes (Cornille et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Unless otherwise mentioned, cells were cultured in the presence of pantethine (0.5 or 1 mM) or pantetheine (1 mM) for 18 h; previous ex vivo treatments showed that maximal cellular effects were obtained under these conditions without side effects (Penet et al, ; Cornille et al, ). Pantethine has been also used at a lower concentration, however, with a longer incubation time (48 h).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated this by adding propionate to generate propionyl-CoA, but can be extended to other lower-abundance CoA species, such as by adding β-hydroxybutyrate to generate β-hydroxybutyryl-CoA (Fig. 5), an important intermediate in fatty acid oxidation and ketogenesis 64,65 . In addition, cells can be subjected to different biological perturbations or toxicological insults to increase and decrease particular CoA species or to generate xenobiotic-CoA adducts such as menadione-CoA (Fig.…”
Section: Introductionmentioning
confidence: 88%
“…Moreover, pantethine circumvented the impairment of fatty acid β-oxidation in rat liver mitochondria and microvessels of the brain (Morisaki et al, 1983). It has been shown recently that pantethine mitigated MPTP neurotoxicity in the mouse via the enhancement of fatty acid β−oxidation, leading to increased levels of circulating ketone bodies and improved mitochondrial function (Cornille et al, 2010). In addition, pantethine attenuates MPTPinduced neuroinflammation, as shown by reduced expression of macrophage antigen-1 (MAC-1), a critical trigger of microglial activation associated with neurodegeneration (Pei et al, 2007) (Fig.…”
Section: Pantethinementioning
confidence: 99%